2015
DOI: 10.1590/1806-9282.61.05.411
|View full text |Cite
|
Sign up to set email alerts
|

Adjuvant treatment delay in breast cancer patients

Abstract: Background: to evaluate if time between surgery and the first adjuvant treatment (chemotherapy, radiotherapy or hormone therapy) in patients with breast cancer is a risk factor for lower overall survival (OS). Method: data from a five-year retrospective cohort study of all women diagnosed with invasive breast cancer at an academic oncology service were collected and analyzed. Results: three hundred forty-eight consecutive women were included. Time between surgery and the first adjuvant treatment was a risk fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 17 publications
0
22
0
Order By: Relevance
“…Retrospective studies examining the impact of adjuvant chemotherapy wait times on survival and patient outcomes have had mixed results, which may be attributed to differences in patient populations, disease-specific factors, variability in the adjuvant treatment administered, and overall patient health status. [7][8][9][10][11][12]17,18 However, emerging data suggest that, particularly for patients at higher risk of recurrence, including those with higher-stage disease, HER2positive or TNBC subtypes, or a high proliferative rate, delayed time from surgery to chemotherapy can adversely impact outcomes. [6][7][8][9][10][11] Gagliato et al 10 found that patients with stage II disease experienced an 18% increase in the risk of distant relapse-free survival when treatment was initiated 31 to 60 days after surgery (hazard ratio, 1.18; 95% CI, 1.03-1.34) compared with when therapy was initiated within 30 days of surgery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Retrospective studies examining the impact of adjuvant chemotherapy wait times on survival and patient outcomes have had mixed results, which may be attributed to differences in patient populations, disease-specific factors, variability in the adjuvant treatment administered, and overall patient health status. [7][8][9][10][11][12]17,18 However, emerging data suggest that, particularly for patients at higher risk of recurrence, including those with higher-stage disease, HER2positive or TNBC subtypes, or a high proliferative rate, delayed time from surgery to chemotherapy can adversely impact outcomes. [6][7][8][9][10][11] Gagliato et al 10 found that patients with stage II disease experienced an 18% increase in the risk of distant relapse-free survival when treatment was initiated 31 to 60 days after surgery (hazard ratio, 1.18; 95% CI, 1.03-1.34) compared with when therapy was initiated within 30 days of surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies suggest that delays in adjuvant chemotherapy initiation greater than 49 to 90 days after surgery may be associated with inferior outcomes, particularly among patients with triple-negative breast cancer (TNBC), HER2-positive subtypes, and higher-stage tumors. [7][8][9][10][11][12] A meta-analysis conducted by Yu et al 13 suggested that overall survival decreases by 15% for every 4-week delay in chemotherapy initiation. Although these retrospective data must be interpreted carefully given potential confounders and selection bias, from a patient-centered perspective, delays to chemotherapy initiation also can adversely impact patient satisfaction and increase stress and anxiety.…”
Section: Introductionmentioning
confidence: 99%
“…Most Brazilian studies of SD were performed in the southern, south-eastern and central-western regions of the country (Trufelli et al, 2007;Souza et al, 2008;Trufelli et al, 2008;Rezende et al, 2009;Lourenço, 2010;Soares et al, 2012;Barros et al, 2013;Oshiro et al, 2014;Guerra et al, 2015;Souza et al, 2015;Trufelli et al, 2015;Lopes et al, 2017). By contrast, only a few studies of SD focused on populations in the Brazilian northeastern region that is experiencing increasing disease incidence (Cavalcanti et al, 2012;Paiva et al, 2015;Ferreira et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Delay in time from diagnosis to treatment in several cancers can lead to adverse outcomes, especially in curative settings. For instance, in breast and colon cancer, when adjuvant chemotherapy is indicated, delay between curative surgeries to adjuvant chemotherapy treatment leads to a decline in cure rate [23,24].…”
Section: Consequences Of Longer Time From Diagnosis To Treatmentmentioning
confidence: 99%